The Effectiveness Of Jeopardy Game To Teach Writing (An Experimental Study At Indonesian Seventh Grade Students) - Gusnur Faridah, Meutia; Dangin, Dangin (International Journal of Educational Research & Social Sciences, 2023)
This study was conducted to determine the effectiveness of using Jeopardy game (teaching and learning media) in writing skill for simple present tense topic. The method used for research was quasi-experimental with two group pretest-posttest. The participants of this study were Indonesian students at seventh grades. The research was conducted by 8 meetings, 6 meetings for treatments and 2 meetings for pretest-posttest. The research data collection used normality test of ShapiroWilk, a test of test on SPSS program. The result of the research showed the different significance before and after treatment with data analysis criteria of t-test showed a t of -6.406 and the probability (p) <0.05 was 0.00. The study showed the effectiveness of using Jeopardy game to teach simple present tense in writing skills.